2003
DOI: 10.1021/ja0353311
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Surface Enhanced Resonance Raman Spectroscopy of the Enhanced Green Fluorescent Protein

Abstract: In the present contribution, we demonstrated that surface-enhanced resonance Raman scattering spectra from single green fluorescent proteins (GFPs) were obtained. The most important findings are the direct detection of the conversion between a deprotonated and a protonated form of the chromophore at the single-molecule level via the corresponding vibrational fingerprints, and the fact that the enhanced green fluorescent protein (EGFP) also shows a high surface enhanced resonance Raman scattering (SERRS) signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
126
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(132 citation statements)
references
References 29 publications
3
126
1
Order By: Relevance
“…The nature of these dark states is still not clear, although changes in the protonation state of the chromophore have been suggested [46,97]. In a report using surface-enhanced resonance Raman measurements, the signatures of the protonated and deprotonated chromophore were found to change on time scales similar to that of fluorescence blinking [101]. Nevertheless, the attribution of blinking to changes in the protonation state has been questioned by the finding that the blinking rates on the millisecond to second time scale were insensitive to pH over a large range [98].…”
Section: Single Vfp Intensity Trajectoriesmentioning
confidence: 99%
“…The nature of these dark states is still not clear, although changes in the protonation state of the chromophore have been suggested [46,97]. In a report using surface-enhanced resonance Raman measurements, the signatures of the protonated and deprotonated chromophore were found to change on time scales similar to that of fluorescence blinking [101]. Nevertheless, the attribution of blinking to changes in the protonation state has been questioned by the finding that the blinking rates on the millisecond to second time scale were insensitive to pH over a large range [98].…”
Section: Single Vfp Intensity Trajectoriesmentioning
confidence: 99%
“…The protein GFP was studied using SERRS at the single molecule level [30], and in this case it was observed that the spectrum changes with time. This spectral change was also observed with SERS studies on Cytochrome C extracted from yeast [31].…”
Section: Sers Of Large Biological Moleculesmentioning
confidence: 99%
“…The EGFP-rhodanese chimera was generated by digesting the PCR product with HindIII and inserting it into the pBAD/HisA(EGFP) vector that was previously digested by the same enzyme, treated with calf intestinal alkaline phosphatase, and purified. The pBAD/HisA(EGFP) vector was previously constructed by removing the gene for EGFP(Q185H) from pEGFP (Clontech, Saint-Germain-en-Laye, France) into the PstI/EcoRI sites of pBAD/HisA (Invitrogen) as described (25), thereby adding to the protein an N-terminal tail that contains a His 6 -tag. A stop codon between EGFP and rhodanese was removed by using site-directed mutagenesis performed with a QuikChange kit (Stratagene, La Jolla, CA) and the oligonucleotides 5Ј-CGGCATGGACGAGCTGTACA AG*A A A-GCGGCCGCGACTCTAGA AT TCG-3Ј (forward) and 5Ј-CGAATTCTAGAGTCGCGGCCGCTTT*CTTGTACAG-CTCGTCCATGCCG-3Ј (reverse).…”
Section: Methodsmentioning
confidence: 99%